Starość w nauczaniu św. Bazylego Wielkiego - Czyżewski, Bogdan (Vox Patrum, 2011)
Although St. Basil did not live 50 years, the topic of the old age appears in his works quite often. On the other hand, it is clear that Basil does not discuss this issue in one particular work or in the longer argumentation. The fragmentary statements about old age can be found in almost all his works, but most of them can be found in the correspondence of Basil. In this paper we present the most important ad the most interesting aspect of teaching of Basil the Great. As these certificates show that the bishop of Caesarea looked at the old age maturely, rationally estimated passage of time, which very often makes a man different. He experienced it, for example as a spiritual and physical suffering, which often were connected with his person. He saw a lot of aspect of the old age, especially its advantages – spiritual maturity and wisdom. What is more, he pointed also to passage of time, which leads a man to eternity, which should be prepared to, regardless how old he is. In his opinion fear is not seen opinions of St. Basil present really Christian way of thinking, well-balanced and calm.